2015
DOI: 10.1021/jp511431q
|View full text |Cite
|
Sign up to set email alerts
|

Sulfation and Cation Effects on the Conformational Properties of the Glycan Backbone of Chondroitin Sulfate Disaccharides

Abstract: Chondroitin sulfate (CS) is one of several glycosaminoglycans that are major components of proteoglycans. A linear polymer consisting of repeats of the disaccharide -4GlcAβ1-3GalNAcβ1-, CS undergoes differential sulfation resulting in five unique sulfation patterns. Because of the dimer repeat, the CS glycosidic “backbone” has two distinct sets of conformational degrees of freedom defined by pairs of dihedral angles: (ϕ1, ψ1) about the β1-3 glycosidic linkage and (ϕ2, ψ2) about the β1-4 glycosidic linkage. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 64 publications
(135 reference statements)
5
50
0
Order By: Relevance
“…By contrast, all of the disulfated CS disaccharides revealed the greatest conformational rigidity . Moreover, it has been reported that in contrast to the 6‐ O ‐sulfation, the addition of a sulfate moiety to the position at the 4 C of the GalNAc residue in the monosulfated disaccharide significantly reduced the rotation of the disaccharide backbone compared to the geometry of the unsulfated disaccharide . These restrictions affected the flexibility of the backbone at the reducing side, but especially at the non‐reducing side of the 4‐ O ‐sulfated GalNAc residue .…”
Section: Monosulfated Disaccharides Provide Interaction Surfaces For mentioning
confidence: 96%
See 4 more Smart Citations
“…By contrast, all of the disulfated CS disaccharides revealed the greatest conformational rigidity . Moreover, it has been reported that in contrast to the 6‐ O ‐sulfation, the addition of a sulfate moiety to the position at the 4 C of the GalNAc residue in the monosulfated disaccharide significantly reduced the rotation of the disaccharide backbone compared to the geometry of the unsulfated disaccharide . These restrictions affected the flexibility of the backbone at the reducing side, but especially at the non‐reducing side of the 4‐ O ‐sulfated GalNAc residue .…”
Section: Monosulfated Disaccharides Provide Interaction Surfaces For mentioning
confidence: 96%
“…GlcA‐GalNAc and GalNAc‐GlcA) were found to display the greatest backbone flexibility compared to the corresponding sulfated analogues . By contrast, all of the disulfated CS disaccharides revealed the greatest conformational rigidity . Moreover, it has been reported that in contrast to the 6‐ O ‐sulfation, the addition of a sulfate moiety to the position at the 4 C of the GalNAc residue in the monosulfated disaccharide significantly reduced the rotation of the disaccharide backbone compared to the geometry of the unsulfated disaccharide .…”
Section: Monosulfated Disaccharides Provide Interaction Surfaces For mentioning
confidence: 97%
See 3 more Smart Citations